Postmetamorphic ontogenetic allometry and the evolution of skull shape in Nest‐building frogs Leptodactylus (Anura: Leptodactylidae). Issue 5 (29th July 2019) - Duport‐Bru, Ana S.; Ponssa, María L.; Vera Candioti, Florencia
Abstract: Allometry constitutes an important source of morphological variation. However, its influence in head development in anurans has been poorly explored. By using geometric morphometrics followed by statistical and comparative methods we analyzed patterns of allometric change during cranial postmetamorphic ontogeny in species of Nest‐building frogs Leptodactylus (Leptodactylidae). We found that the anuran skull is not a static structure, and allometry plays an important role in defining its shape in this group. Similar to other groups with biphasic life‐cycle, and following a general trend in vertebrates, ontogenetic changes mostly involve rearrangement in rostral, otoccipital, and suspensorium regions. Ontogenetic transformations are paralleled by shape changes associated with evolutionary change in size, such that the skulls of species of different intrageneric groups are scaled to each other, and small and large species show patterns of paedomorphic/peramorphic features, respectively. Allometric trajectories producing those phenotypes are highly evolvable though, with shape change direction and magnitude varying widely among clades, and irrespective of changes in absolute body size. These results reinforce the importance of large‐scale comparisons of growth patterns to understand the plasticity, evolution, and polarity of morphological changes in different clades. Abstract : Cranial ontogenetic and evolutionary allometric patterns during postmetamorphic development in Leptodactylus frogs. RESEARCH HIGHLIGHTS: The skulls of Leptodactylus frogs undergo deep shape/size changes after metamorphosis. Small/large species show some paedo/peramorphic cranial features. Allometric trajectories vary among species and irrespective of body size evolution.